Psoas abscess: Rare complication of Crohn’s disease - Piñeyro, Alberto; Carriquiry, Luis A; Navarrete, Héctor (Cirugía del Uruguay, 1991)
A case of psoas abscess, an infrequent complication of Crohn's ileocolitis, is presented. A brief revision of the etiological, anatomopathological and therapeutical concepts of this disease is made, pointing out the role played by exeresis surgery when in the tace of complications